Performance enhancement of full inorganic Sb2S3 solar cells with MnS hole transport layers - Minghong Rui; Hangyu Li; Yuan Li; Wenqi Li; Sumei Wang (Next Energy)
The hole transport layer (HTL) is a crucial component in planar antimony sulfide (Sb2S3) solar cell. However, the issue of high cost, poor environmental stability and toxic benzene-based solvents for preparation represent significant challenges for the efficient organic HTLs. In contrast, low-cost and environmentally friendly inorganic hole transport materials have garnered considerable attention due to their excellent carrier mobility and environmental stability. Herein, thermal evaporated inorganic manganese sulfide (MnS) thin films were prepared as HTL for full inorganic Sb2S3 solar cell. The effects of post-annealing treatment on the structure, photoelectric properties of MnS films and device performance were investigated. The post-annealing treatment enables MnS HTL to exhibit high carrier mobility and suitable energy band matching characteristics, thereby suppressing the internal charge recombination and reducing the voltage loss in the device. This ultimately results in a high photovoltaic conversion efficiency (PCE) of 5.66%, which is more than a twofold increase in efficiency compared to that of device with unannealed MnS HTL. Furthermore, the optimal MnS HTL-based Sb2S3 solar cell demonstrated superior environmental stability (around 5.59% degradation in 30 days), compared to that of device with organic Spiro-OMeTAD HTL (around 20% degradation in 30 days). The study offers a material choice and post-processing solution for the development of high-efficiency all-inorganic Sb2S3 solar cells.